PENENTUAN ASAM OKSALAT SECARA SPEKTROFOTOMETRI DENGAN METODE METILEN BIRU - Irmanto; Suyata (Molekul, 2006)
A spectrophotometric method for the determination of oxalic acid has been developed, based on its catalytic effect on the redox reaction between methylene blue and sulphide, measured at the maximum absorption wavelength of 664 nm. Under the optimum conditions of 3 mL of 31 % formaldehyde; 0.8 mL of 0,067 M EDTA - Triethanolamine; 1.2 mL of 0,010 M sulphide; 2 mL of 0,0010 % methylene blue at 20 oC for 1 minute a detection limit of 0,43 mg/mL for oxalic acid determination was obtained. This method can be applied to determination of trace level of oxalic acid.